Factors leading to being unfriended on Facebook among adults / Siti Hajar Abd Aziz ... [et al.] - Abd Aziz, Siti Hajar; Batrisyia, Auni; Zulkifli, Farhana; Ikhzan, Faiza; Fauzul, Najeeha; Hassan, Mohd Sufiean (Faculty of Communication & Media Studies, 2022)
The social media is a popular mean to connects with friends and families. Studies shown that it provides social and emotional support to those connected, apart from acting as an information resources such as news, products, and services. This paper is interested to investigate the users' behaviour and aim to study the factors leading to being unfriended on Facebook among adults. Social networking sites such as Facebook are chosen as adults widely use them. This study used Expectancy Violations Theory (EVT) as foundations theories for humans that create comfort or discomfort to one another. The minimum sample was collected using Google Form. The study involved 110 respondents aged 20 to 31 and above from men and women in Malaysia. A cross-sectional questionnaire was used for data collection. All variables were measured through data sum from the Google Form Gantt chart. The data stating a few factors that might lead to reasons being unfriended on Facebook. The results show that 54.5% of them agreed that the main reason for being unfriended on Facebook is due to people's personalities. Almost 75.5% of the respondents claimed to have ever experienced being unfriended, and 68.2% of it came from strangers. However, strangers or not, it is widely considered that being unfriended triggers an act of expectancy violations that could vary in terms of situations and the reasons behind it. Thus, studies suggest that being unfriended is negative and creates discomfort among the parties.